Natural Polymers from Plants are Used in Wound- Healing Dressings and Gels (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
Natural polymers derived from plants have gained significant attention in the field of wound healing due to their biocompatibility, biodegradability, and ability to promote tissue regeneration. These polymers, such as alginate, chitosan, and cellulose, possess unique properties that facilitate moisture retention, provide a protective barrier against infections, and enhance the healing process. The incorporation of natural plant extracts into these polymeric matrices further enhances their therapeutic potential by introducing bioactive compounds that can reduce inflammation and accelerate healing. This review explores the various types of natural plant-based polymers used in the formulation of wound-healing dressings and gels, highlighting their mechanisms of action, advantages over synthetic alternatives, and potential applications in modern medicine. The findings suggest that the integration of natural polymers in wound care not only improves healing outcomes but also aligns with the growing demand for sustainable and eco-friendly medical products.